Study of crack formation and limit equilibrium of reinforced concrete florr slab shell - A. V. Selivanov; F. F. Reger; I. A. Chakurin (Вестник СибАДИ)
Introduction. Experimental studies of crack formation and limit equilibrium of a reinforced concrete floor slab-shell, developed by the authors, were carried out.Materials and methods. The studies were carried out on reinforced concrete models made on a scale of 1:5. Results. During the tests, three stages of the stress-strain state were established: the first is the elastic stage of concrete tensile work in the lower part of the longitudinal contour ribs; the second is the stage of formation and opening of cracks; the third is the stage of destruction.Discussion and conclusions. The first stage is observed from the beginning of loading until the moment of cracks formation in the longitudinal ribs, the second is between the end of the first stage and the beginning of the destruction of the ribs, the third is during the destruction of the flange and ribs of the models.